With Gilbert & George in Moscow - Farson, Daniel, 1927-1997 (London : Bloomsbury, 1991)
Farson neemt ons met het gekende kunstenaarskoppel Gilbert & George mee op een reis door Moskou.
Includes index.
Spine title: With Gilbert and George in Moscow.
Keywords: Farson, Daniel, -- 1927- -- Travel -- Russia (Federation) -- Moscow; Gilbert & George -- Exhibitions; Conceptual art -- Public opinion -- England; Conceptual art -- England -- Exhibitions; Public opinion -- Russia (Federation) -- Moscow; Moscow (Russia) -- Description and travel